Barça-Madrid: a global rivalry. Analysis of the derby through the Spanish written press - Coterón López, Javier; Bello Garrido, Mattew Fernando (Estudios sobre el Mensaje Periodístico, 2012)
The relationship between football and the media clearly shows interdependence signs. The aim of this study was to determine the treatment given by the major Spanish written media during the coverage of four Barça-Madrid derbies in April and May 2011. A content analysis of newspapers El Pais, Marca, Sport and La Vanguardia was conducted, studying the characterization of the message and the influences that on the speech-sporting journalism have certain factors, mainly economic and sociopolitical. The study shows the changes concerning the Spanish press in covering a global impact phenomenon.